The effect of heat treatment on creep behavior of GTD-111 superalloy welded by pulsed Nd:YAG laser using small punch test. (April 2021) - Taheri, Morteza; Halvaee, Ayyub; Kashani Bozorg, Seyed Farshid; Golezani, Ali Salemi; Liavoli, Rohallah Panahi; Kashi, Ali Akbar
Highlights: The cause of crack formation in the HAZ of GTD-111 can be attributed to γ′, γ-γ′, MC, and Cr-Mo phases. The γ′ phase is the most effective phase in increasing the creep resistance due to the obstruction against the movement of dislocations. It is strongly recommended to prevent GB slippage and consequent GB failure due to creep by removing crack-sensitive phases in the HAZ through heat treatment before welding. Abstract: This work is about the evaluating creep characterizations of GTD-111 superalloy, and its weldment, which has high demand in use in turbine blades of aero-engines and land-based gas turbine industries. For this purpose, plates with a thickness of 3 mm have subjected to Nd:YAG pulsed-laser welding. Test specimens were machined from different parts of weldments and prepared in the shape of disks with a thickness of 0.5 mm, including weld metal, heat-affected zone, and base metal. Small punch creep tests were carried out at 700 °C with loads of 350 N and 450 N to find the weakest location in creep consideration of GTD-111 weldment. Analysis of creep diagrams based on time-displacement showed that the weld metal has the highest creep life due fine γ′ particles and MC carbide. The HAZ of the heat-treated specimen showed a longer creep life of about 17 h than the cast specimen. This was due to the reduction of harmful phases for welding, including γ′, γ-γ′, MC, and Cr-M, which were the leading cause of the defect and reduced creep life in HAZ.